Sustainable Implementation of Universal Design in Slums: A Case Study of Taman Odah Bekesah, Samarinda - Rahim, Dzulfajrie; Permana, Asep Yudi; Sari, Diah Cahyani Permana (Proceeding of International Joint Conference on UNESA, 2025)
The city of Samarinda has a vast natural landscape, and there are many open spaces that have not been optimally utilized. City parks and neighborhood parks, along with the built infrastructure, serve as spaces for activities in open areas that must accommodate inclusive principles and apply universal design. These parks are part of public spaces, which are closely related to the social life within them. In Taman Odah Bekesah, it was found that several built infrastructures have not optimally applied universal design. The aim of this research is to examine and analyze the implementation of universal and inclusive design principles at Taman Odah Bekesah using a qualitative descriptive method. This research can serve as a form of architectural and regional critique in the context of public spaces to support environmental and social sustainability. The results of this research indicate that the infrastructure built in two segments of Taman Odah Bekesah has not fully implemented universal design.